The Impact of CEO Compensation on Nonprofit Donations - Balsam, Steven; Harris, Erica E. (The Accounting Review, 2014)
ABSTRACT In this paper we show that supporters reduce donations to nonprofits subsequent to disclosure of high executive compensation. We find evidence consistent with large, sophisticated donors actively seeking out and reacting to compensation information made available in IRS Form 990, while smaller donors react to compensation disclosures in the media. Additional analysis indicates that these results vary systematically across nonprofits, as we find a stronger negative relation in nonprofits classified as more charitable, and a weaker relation in nonprofits that provide services to their donors. In contrast neither grantors nor patrons appear to react to executive compensation disclosures. Data Availability: All data are available from public sources.